2017
DOI: 10.21037/cdt.2017.09.19
|View full text |Cite
|
Sign up to set email alerts
|

Re-intervention for occluded iliac vein stents

Abstract: Iliac vein stenting has become more frequent with improved diagnostic capabilities of intra-vascular ultrasound (IVUS) for recognizing May-Thurner syndrome, chronic venous insufficiency (CVI) and thrombus. In this manuscript, we discuss the reasons for initial stenting, with long-term outcomes and some of the associated pitfalls. The best techniques for re-intervention when iliac stents become occluded will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Many cases of iliac vein compression have been treated successfully by stenting 4 . However, our experience in this case showed that prolonged dilatation of the compressed lesion was not effective in restoring the geometry of the vein to the round shape necessary for smooth passage of the leadless pacemaker device.…”
Section: Discussionmentioning
confidence: 73%
“…Many cases of iliac vein compression have been treated successfully by stenting 4 . However, our experience in this case showed that prolonged dilatation of the compressed lesion was not effective in restoring the geometry of the vein to the round shape necessary for smooth passage of the leadless pacemaker device.…”
Section: Discussionmentioning
confidence: 73%
“…According to one study, severe in-stent restenosis, defined as less than 50%, occurred in 5% of stented limbs at 72 months, with thrombophilia by itself not being a risk factor. They noted that the largest contributor to re-stenosis was actually the underlying extent of thrombotic disease [ 19 ]. It can be deduced that those with May-Thurner Syndrome plus underlying atherosclerosis may be at a higher risk of needing repeat intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention has advanced from open techniques to more modern endovascular therapy with angioplasty and stenting, followed by anticoagulation. In eligible patients, catheter-directed thrombolysis or mechanical thrombectomy are excellent options to remove the thrombus burden, visualize the affected area, and stent the stenotic lesion [17][18][19]. Lifelong anticoagulation is often recommended after surgical intervention, though there is some debate.…”
Section: Figure 1: Compression Of the Left Iliac Vein By The Right Co...mentioning
confidence: 99%
“…Insufficiency coverage of the lesion is important factor contributing to venous stent failure (7,8). A study conducted by Raju et al focused on re-interventions for non-occlusive stent malfunction, spanning a 10-year period and involving 1,085 limbs that underwent femoral-iliac-caval stenting (9).…”
Section: Insufficient Coverage Of the Lesionmentioning
confidence: 99%